Leptin levels in obese women with and without type 2 diabetes mellitus. Issue 5 (2004) - Buyukbese, Mehmet Akif; Cetinkaya, Ali; Kocabas, Ramazan; Guven, Aytekin; Tarakcioglu, Mehmet
Abstract : INTRODUCTION : The role of leptin has been more clear in the endocrinology area after the discovery of its secretion from the adipose tissue. The aim of the study is to investigate the leptin levels in obese women in whom type 2 diabetes mellitus were present or absent. Materials and methods : Thirty-five obese women with type 2 diabetes mellitus (group 1) and 34 obese women without type 2 diabetes mellitus (group 2) were enrolled in the study. In both groups the body mass index (BMI), waist circumference, and waist-to-hip ratio were measured. Leptin, HbA1c, creatinine and the lipid profile were assessed. Results : Leptin was found to be statistically significantly lower in group 1 than in group 2 (40.22±17.77 ng/ml versus 50.12±15.51 ng/ml, respectively;p = 0.019 ). It was well correlated with BMI in group 1 (r = 0.60, p = 0.0001 ). In group 1 also, correlation of leptin was moderate with creatinine and high-density lipoprotein-cholesterol (r = 0.36, p = 0.037 versusr = 0.37, p = 0.027, respectively), whereas triglyceride had a negative correlation (r = -0.34, p = 0.046 ). In group 2, the only significant correlation with leptin was BMI (r = 0.41, p = 0.02 ). Leptin was also significantly lower in 17 subjects with poorly controlled diabetes mellitus than in 18 well-controlled diabetics (33.54±15.82 ng/ml versus 44.61±17.54 ng/ml, respectively;p = 0.038 ). Conclusion : Since leptin is lower in obese women with diabetes than without diabetes and additionally it is even lower in the poorly controlled diabetes subgroup, we think that further studies are required to make clear the issue for lower leptin levels, whether it is a reason or an outcome.